Invisible in the smart city: Using participatory design methods for age-friendly solutions - van Leeuwen, Cora; Devis Clavijo, Juanita; Mariën, Ilse; Jacobs, An (Frontiers in Sustainable Cities, 2022)
Older adults face unique challenges and have differing needs when navigating the urban environment. At the same time, civil servants and policymakers in cities are facing difficulties in promoting age-friendly initiatives due to the lack of knowledge, data, and tools about and for older adults. In this context, smart cities can play a key role in increasing the participation of older adults (i.e., 65 years and older). They can also collect the necessary information on older adults for policymakers and civil servants. Policymakers and civil servants in smart cities are tasked to uncover the needs and to provide informed policy-making geared towards addressing the needs of this population. This task is made more difficult by several existing issues such as aggregated nonage-specific big data, lack of data altogether, and a disparity in access and use of digital technology. This paper endeavors to provide a methodology to ensure that the older adults are represented in the collected data and the translation of this data into automatic policy-making decisions. The Participation for Policy for Older Adults (PAR4POA) method introduces older adults’ perspectives from the start of the project and its iterative approach means that older adults will share their needs and values with policymakers at different stages of a project. We will provide examples of how this method was used within an H2020 URBANAGE project. The use of this method enabled the co-creation of smart city solutions targeted to address the needs of older citizens in the context of 3 European regions. The proposed method was adjusted from the original PAR4P method by adding additional consultations with older adults to understand their lifeworld and how data collection via digital technology could be introduced to be accepted by older adult users. Furthermore, the adjustment ensures that the results could lead to automatic policy-making decisions. The PAR4POA method is specifically altered for the situation of older adults but could easily be used to include other marginalized populations. Ensuring participation in the automatic policy-making arena will empower marginalized populations and provide representation in data previously not provided.